The Impact of Traffic in the Medan Industrial Estate on the Social and Economic Community of Amplas Village, Percut Sei Tuan, Deli Serdang Regency, North Sumatra - Ardiles Hasianta Meka; Abdi Sugiarto; Wahyu Hidayat (Journal of Information Technology, computer science and Electrical Engineering, 2025)
This study aims to analyze the impact of traffic in the Medan Industrial Estate on the quality of life of the community in Amplas Village, Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The research method uses a descriptive qualitative approach to understand the traffic impact of the Medan Industrial Estate (KIM), which includes in-depth interviews and questionnaires involving respondents from the local community. The results showed that the presence of industry had a positive impact on the community's economy, with 70.78% of respondents expressing improvements in economic structure and 100% of respondents agreeing that industry has reduced the unemployment rate through job creation. However, negative impacts such as air pollution and noise due to increased traffic are also felt significantly, which has the potential to reduce the quality of life of the community.The results showed that 75.60% of respondents reported an increase in income, but they also faced challenges such as congestion that led to an increase in business operating costs and a decrease in property values. Public perceptions of environmental safety and comfort indicate concern about the risk of accidents and health impacts due to pollution. This study recommends the need for more comprehensive traffic planning and attention to the environmental impact of industrial activities. It is hoped that with the right mitigation measures, the quality of life of the people in Amplas Village can be improved without sacrificing sustainable economic growth.